2007
DOI: 10.1126/science.1144885
|View full text |Cite
|
Sign up to set email alerts
|

A Vasculature-Associated Niche for Undifferentiated Spermatogonia in the Mouse Testis

Abstract: Mammalian spermatogenesis produces numerous sperm for a long period based on a highly potent stem cell system, which relies on a special microenvironment, or niche, that has not yet been identified. In this study, using time-lapse imaging of green fluorescent protein-labeled undifferentiated spermatogonia (A(undiff)) and three-dimensional reconstitution, we revealed a biased localization of A(undiff) to the vascular network and accompanying Leydig and other interstitial cells, in intact testes. Differentiating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
359
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(374 citation statements)
references
References 28 publications
15
359
0
Order By: Relevance
“…The niche microenvironment is provided by the somatic Sertoli cells, the basement membrane and cellular components of the interstitial space between the seminiferous tubules. More specifically, these extrinsic signals include growth factors produced by Sertoli cells (Simon et al, 2007), adhesion molecules linking the SSCs to basement membrane components such as laminin (Orwig et al, 2002), and stimuli from the vascular network and interstitial cells (Yoshida et al, 2007). Spermatogonial stem cells are located at the periphery of the seminiferous epithelium, in contact with the basement membrane and Sertoli cells.…”
Section: Spermatogenesis and The Spermatogonial Stem Cell Nichementioning
confidence: 99%
“…The niche microenvironment is provided by the somatic Sertoli cells, the basement membrane and cellular components of the interstitial space between the seminiferous tubules. More specifically, these extrinsic signals include growth factors produced by Sertoli cells (Simon et al, 2007), adhesion molecules linking the SSCs to basement membrane components such as laminin (Orwig et al, 2002), and stimuli from the vascular network and interstitial cells (Yoshida et al, 2007). Spermatogonial stem cells are located at the periphery of the seminiferous epithelium, in contact with the basement membrane and Sertoli cells.…”
Section: Spermatogenesis and The Spermatogonial Stem Cell Nichementioning
confidence: 99%
“…The major contributor to the SSC niche is Sertoli cells, although the effects of Leydig and myoid cells are not negligible (Yoshida et al, 2007). Sertoli cells reside in the seminiferous tubules in close contact with spermatogonia.…”
Section: Extrinsic Factorsmentioning
confidence: 99%
“…A vasculature-associated niche also plays critical roles in maintaining undifferentiated spermatogonia in the mouse testes (Yoshida et al, 2007). Undifferentiated spermatogonia preferentially reside in a specific area of the basal compartment within the seminiferous tubules.…”
Section: Extrinsic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Previous studies have shown that spermatogenesis involves the detachment of spermatogonia from the basement membrane and their subsequent migration towards the lumen of seminiferous tubules. 2,3 Although mechanisms underlying the maintenance and selfrenewal of SSCs have been explored by many research groups, 1-3 the signaling molecules that mediate the decision of SSCs to differentiate rather than self-renewal remain largely unknown. The balance between self-renewal and differentiation of SSCs must be tightly controlled to maintain normal homeostasis in the normal seminiferous epithelium.…”
Section: Introductionmentioning
confidence: 99%